Health effects of organic farming, review of literature since 2005-Revision - Maria Groot (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
In 2005, a study was carried out with chicks fed either organic feed or conventional feed. The aim of the trial was to see whether there was a difference in health between organic and non-organic fed chickens, as a stepping stone to a study in pigs and ultimately in humans. Thus, the final goal was to see whether organic food has positive health effects on humans. In the study, it appeared that animals fed organic feed showed a stronger immune response after a challenge than animals not fed organic feed. However, the researchers found that no firm conclusions could be drawn about the health status of organically fed animals. Based on these results, it was decided not to commission a follow-up study because the differences would be too small. The current knowledge and insights may give new reasons for follow-up research. For this purpose, a report was published with a summary of the original research and subsequent publications, as well as results from literature since 2005 on the health effects of organic feed for animals and organic products for humans. After the 2005 study, no comparable animal studies were carried out with organic and conventional feed. It is precisely in the case of animals that only the feed can differ, which can provide valuable insight into the effects of using only organic nutrition. Research has been done on the differences in composition between conventional and organic products. Human cohort studies have also been conducted on the effects of organic food on health parameters and the occurrence of various types of cancer. Although most researchers are very cautious about concluding the health effects of organic food, there are several relevant findings on differences in the composition of products, most of which are related to the organic production method. These include no synthetic chemical crop protection agents and fewer biocides as compared to conventional production, more antioxidants, and phenols and fewer antibiotic-resistant germs than conventional food. Moreover, milk has a more beneficial fatty acid pattern. There are some indications that eating organic food lowers the risk of developing certain conditions, such as allergies, metabolic syndrome and obesity, and certain cancers.